2021
DOI: 10.3390/nano11020445
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Cerium Coating Strategy for Titanium Oxide Nanotubes’ Bioactivity Enhancement

Abstract: Despite the well-known favorable chemical and mechanical properties of titanium-based materials for orthopedic and dental applications, poor osseointegration of the implants, bacteria adhesion, and excessive inflammatory response from the host remain major problems to be solved. Here, the antioxidant and anti-inflammatory enzyme-like abilities of ceria (CeOx) were coupled to the advantageous features of titanium nanotubes (TiNTs). Cost-effective and fast methods, such as electrochemical anodization and drop ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…In addition, XPS was used to determine the Ca/P, O/P, and O/Ca ratios for all samples after their immersion in SBF, confirming the formation of HA [ 68 ]. Using XPS, insights into the chemical interactions during the formation of the coating can be gained, which is crucial for understanding the final performance of the coating [ 69 , 70 , 71 ]. De Santis et al [ 69 ] used XPS to analyze Ti implant samples with TNT-Ce n (n = 1, 3, 6, 9, and 12, based on the number of depositions) coatings.…”
Section: Interaction and Morphology Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, XPS was used to determine the Ca/P, O/P, and O/Ca ratios for all samples after their immersion in SBF, confirming the formation of HA [ 68 ]. Using XPS, insights into the chemical interactions during the formation of the coating can be gained, which is crucial for understanding the final performance of the coating [ 69 , 70 , 71 ]. De Santis et al [ 69 ] used XPS to analyze Ti implant samples with TNT-Ce n (n = 1, 3, 6, 9, and 12, based on the number of depositions) coatings.…”
Section: Interaction and Morphology Studiesmentioning
confidence: 99%
“…Using XPS, insights into the chemical interactions during the formation of the coating can be gained, which is crucial for understanding the final performance of the coating [ 69 , 70 , 71 ]. De Santis et al [ 69 ] used XPS to analyze Ti implant samples with TNT-Ce n (n = 1, 3, 6, 9, and 12, based on the number of depositions) coatings. It was reported that Ti was fully oxidized to Ti 4+ due to the pure TNTs employed.…”
Section: Interaction and Morphology Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceria has been studied as an additive for well-known materials used in medical implants in virtue of its antioxidant and anti-inflammatory properties and to favor the direct osseointegration at the biointerface. This concept was applied to titania alloys [ 181 ], and nanotubes, and an increased level of early hydroxyapatite precipitation was noted from simulated body fluid [ 182 ]. Furthermore, ceria-stabilized zirconia has been proposed as a promising biomedical implant material.…”
Section: (Bio)applicationsmentioning
confidence: 99%
“…Results show that the anodization process coupled with the heat treatment provides significant corrosion protection to the SS and the welds. Furthermore, the proposed methodology has distinct advantages of being simple, safe, low-cost, and versatile, making it highly promising in numerous fields [33][34][35].…”
Section: Introductionmentioning
confidence: 99%